2020
DOI: 10.1186/s12915-020-00886-1
|View full text |Cite
|
Sign up to set email alerts
|

The CBP KIX domain regulates long-term memory and circadian activity

Abstract: Background CREB-dependent transcription necessary for long-term memory is driven by interactions with CREB-binding protein (CBP), a multi-domain protein that binds numerous transcription factors potentially affecting expression of thousands of genes. Identifying specific domain functions for multi-domain proteins is essential to understand processes such as cognitive function and circadian clocks. We investigated the function of the CBP KIX domain in hippocampal memory and gene expression using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 131 publications
2
15
0
Order By: Relevance
“…Notably, these ligand-independent “orphan” receptors are robustly up-regulated in the hippocampus within minutes after learning ( 3 , 4 ). The learning-dependent expression of the Nr4a genes is regulated by histone acetylation, which is driven by recruitment of adenosine 3′,5′-monophosphate (cAMP) response element–binding protein (CREB)–binding protein (CBP) ( 9 ) to CREB response elements in the promoters of these genes ( 10 , 11 ). Blocking the expression or inactivating the transactivation function of Nr4a factors is sufficient to impair long-term memory ( 4 , 7 ) and synaptic plasticity ( 12 ), whereas transgenic or pharmacological activation enhances long-term memory ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these ligand-independent “orphan” receptors are robustly up-regulated in the hippocampus within minutes after learning ( 3 , 4 ). The learning-dependent expression of the Nr4a genes is regulated by histone acetylation, which is driven by recruitment of adenosine 3′,5′-monophosphate (cAMP) response element–binding protein (CREB)–binding protein (CBP) ( 9 ) to CREB response elements in the promoters of these genes ( 10 , 11 ). Blocking the expression or inactivating the transactivation function of Nr4a factors is sufficient to impair long-term memory ( 4 , 7 ) and synaptic plasticity ( 12 ), whereas transgenic or pharmacological activation enhances long-term memory ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Per1 , a target of our model, is a circadian regulator gene upregulated by neuronal activity 29 . It has been demonstrated that disrupted activity-dependent binding of CREB to CREB-binding protein (CBP) impairs long-term memory in mice and blunts the transcriptional upregulation of immediate early genes and circadian rhythm genes 30 . Together with our results, this suggests a subset of the activity response is allocated to a group of genes regulating circadian rhythm, and our model extracts this information from the transcriptome to predict expression levels of activity-dependent genes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, synRas mice, in which endogenous Ras activity continues to be regulated and ERK phosphorylation level is upregulated, were found to be more sensitive to light than wild-type mice, because synRas mice showed higher phosphorylation levels of CREB in the SCN induced by light pulses than wild-type mice, especially during the early subjective night period (Serchov et al 2016). Moreover, CBP KIX/KIX mice that do not show stimulus-induced activation of CREB, showed lower locomotor activity levels at the beginning of the active period (Chatterjee et al 2020). Taken together, these results suggest that FCR modified the HFD feeding-induced locomotor activity level decrease at of the time LD switching via the activation of the ERK/ CREB signaling.…”
Section: Discussionmentioning
confidence: 99%